Impact of training systems and rootstocks on yield and quality of white Brazilian hybrid grapes - Neto, Francisco José Domingues [UNESP]; Tecchio, Marco Antonio [UNESP]; Carneiro, Débora Cavalcante dos Santos [UNESP]; Figueira, Ricardo [UNESP]; Rodrigues, João Domingos [UNESP]; Moura, Mara Fernandes; Hernandes, José Luiz; Putti, Fernando Ferrari [UNESP]; Leonel, Sarita [UNESP]; Silva, Marcelo de Souza [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; et al. (Southern Cross Publishing, 2025)
Conservation agricultural practices play a crucial role in improving crop yield and quality. In viticulture, particular attention has been given to the interaction between scion cultivars, rootstocks, and training systems. This study aimed to evaluate the effects of rootstocks and training systems on the yield and quality of the Brazilian hybrid white grapes ‘BRS Lorena’, ‘IAC 116-31 Rainha’, and ‘IAC 21-14 Madalena’. For each cultivar, a randomized block design was adopted using a 2 × 2 factorial scheme, comprising two rootstocks (‘IAC 766 Campinas’ and 106-8 ‘Mgt’) and two training systems (low and high espalier). Physicochemical characteristics of clusters, berries, and seeds, as well as the biochemical composition of the grape skins and pulp, were assessed over two production cycles. The results demonstrated that the appropriate combination of rootstock and training system can significantly influence grape yield and quality. ‘BRS Lorena’ performed best when grafted onto 106-8 ‘Mgt’ under the high espalier system. ‘IAC 21-14 Madalena’ showed stable performance with 106-8 ‘Mgt’, regardless of the training system. For ‘IAC 116-31 Rainha’, the most favorable combination was ‘IAC 766 Campinas’ rootstock with high espalier. These findings provide valuable insights for Brazilian viticulture, supporting the adoption of cultivation practices that enhance both productivity and grape quality.